2008
DOI: 10.1016/j.brainresrev.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular mechanisms involved in the neurotoxicity of opioid and psychostimulant drugs

Abstract: Substance abuse and addiction are the most costly of all the neuropsychiatric disorders. In the last decades, much progress has been achieved in understanding the effects of the drugs of abuse in the brain. However, efficient treatments that prevent relapse have not been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
148
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 198 publications
(149 citation statements)
references
References 163 publications
(203 reference statements)
1
148
0
Order By: Relevance
“…These drugs increase the extracellular concentration of monoamines, such as dopamine, leading to increased dopamine transmission [283]. Dopamine is involved in controlling reward, cognition and movement, explaining why these drugs of abuse affect locomotion [284,285].…”
Section: Psychostimulant Drugs Of Abuse and Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs increase the extracellular concentration of monoamines, such as dopamine, leading to increased dopamine transmission [283]. Dopamine is involved in controlling reward, cognition and movement, explaining why these drugs of abuse affect locomotion [284,285].…”
Section: Psychostimulant Drugs Of Abuse and Pdmentioning
confidence: 99%
“…Amphetamines increase extraneuronal dopamine and other monoamine levels, through a nonͲexocytotic mechanism, by directly interacting with monoaminergic cells [283,286,287]. Due to its structural similarity with dopamine, amphetamine is a substrate for the DAT [288]and, when in low concentrations,itis transported by the DAT to the cytosol.…”
Section: Amphetaminesdopamine and Pdmentioning
confidence: 99%
“…Cocaine may interact directly with mitochondria and other intracellular targets (Heard et al, 2008), after entering the cell due to its positive charge at physiological pH (Cunha-Oliveira et al, 2008). Studies in hepatic mitochondria showed that in vivo cocaine administration decreased state 3 respiration, the respiratory control ratio (RCR) and the activity of complexes I, II/III, and IV (Devi and Chan, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Amphetamines increase extraneuronal dopamine and other monoamine levels, through a nonexocytotic mechanism, by directly interacting with monoaminergic cells [283,287,288]. Because of its structural similarity to dopamine, amphetamine is a substrate for the DAT [289] and, when in low concentrations, it is transported by the DAT to the cytosol.…”
Section: Psychostimulant Drugs Of Abuse and Pdmentioning
confidence: 99%